The Effectiveness Of Developing An Adaptive Physics E-Module In Moodle-Based Blended Learning On Students’ Representation Ability On Thermodynamics Material - Ramadhanty Eka Putri, Swastika; Khumaedi, Khumaedi; Naini Mindyarto, Budi (Edumaspul: Jurnal Pendidikan, 2023)
The research aims to develop adaptive electronic modules using Moodle-based blended learning as a solution to improve representation skills in the school environment. This research combines online and face-to-face learning methods (blended learning) with the use of Moodle as a digital learning platform. Three forms of representation in the concept of physics, are (1) verbal representation; (2) visual representation; and (3) mathematical representation. The formulation of the problem in this research is the characteristics, validity, and effectiveness of the E-module. This module aims to provide learning content that is tailored to the needs and abilities of each individual student. Adaptive features allow students to access materials, assignments, and learning resources appropriate to their skills level. Learning is done through a combination of classroom teaching and e-modules through Moodle. E-module development model uses the research and development method. The research design used is a true experimental design in the form of a "Posttest-Only Control Design". Assessment includes data collection through surveys, observation, and evaluation of learning outcomes. The purpose of the evaluation is to analyze the effectiveness and efficiency of using adaptive e-modules with Moodle based on blended learning to improve students’ representation skills at school. The research results showed that the E-module assessment by experts obtained a content percentage and eligibility criteria of 91.7% (feasible). To determine the level of effectiveness through the t test and comparison of posttest results. This is evidenced by the test using SPSS version 23 which shows a significance value of 0.00 <0.05. In visual representation, a percentage of 87.5% was obtained in a very good category, for mathematical representation, a percentage also was obtained in a very good category, 88.5%, and in verbal representation, a percentage was obtained in a category of 90%, as the greatest. With an average post-test score of 88.8 for the experimental of the class and 74.2 for the control of the class. Adaptive e-modules through Moodle-based blended learning can be an effective choice for increasing representational abilities and facilitating personalized and flexible learning. The results of this study are expected to encourage the development of adaptive learning systems in schools and support the improvement of student learning outcomes.